Accounting Internships and Subsequent Academic Performance: An Empirical Study. - Knechel, W. Robert; Snowball, Doug (The Accounting Review, 1987)
ABSTRACT: This study investigates the impact of student internships on subsequent academic performance. The post-internship course performance of students with internship experience was compared to that of a group of noninterns (matched on grade-point average and hours of coursework completed prior to the internship). Average performance across all courses did not differ significantly between the two groups. Analysis of performance in particular subject areas and courses suggests a tendency for interns to focus their efforts on courses most closely related to their chosen career. However, only in auditing coursework (where substantive knowledge gained from their internship experience should be most applicable) was the performance of interns significantly better than that of the noninterns.